The role of anti-citrullinated protein antibody reactivities in an inception cohort of patients with rheumatoid arthritis receiving treat-to-target therapy - Jonsson, Maria Karolina; Hensvold, Aase Haj; Hansson, Monika; Aga, Anna-Birgitte; Sexton, Joseph; Mathsson-Alm, Linda; Cornillet, Martin; Serre, Guy; Lillegraven, Siri; Fevang, Bjørg-Tilde Svanes; Catrina, Anca Irinel; Haavardsholm, Espen Andre (Arthritis Research & Therapy, 2018)
International audience Background: Anti-citrullinated protein antibody (ACPA) reactivities precede clinical onset of rheumatoid arthritis (RA), and it has been suggested that ACPA reactivities towards distinct target proteins may be associated with differences in RA phenotypes. We aimed to assess the prevalence of baseline ACPA reactivities in an inception cohort of patients with early RA, and to investigate their associations with disease activity, treatment response, ultrasound findings and radiographic damage. Methods: Disease-modifying antirheumatic drug (DMARD)-naïve patients with early RA, classified according to the 2010 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) criteria, were included in the ARCTIC trial and assessed in the present analysis. During follow up, patients were monitored frequently and treatment was adjusted according to a predetermined protocol, starting with methotrexate monotherapy with prednisolone bridging. Analysis of 16 different ACPA reactivities targeting citrullinated peptides from fibrinogen, alpha-1 enolase, vimentin, filaggrin and histone was performed using a multiplex chip-based assay. Samples from 0, 3, 12 and 24 months were analysed. Controls were blood donors with similar characteristics to the patients (age, gender, smoking status). Results: A total of 217 patients and 94 controls were included. Median [25, 75 percentile] number of ACPA reactivities in all patients was 9 [4, 12], and were most prevalent in anti-cyclic citrullinated peptide /rheumatoid factor-positive patients 10 [7, 12]. Disease activity measures and ultrasound scores at baseline were lower in ACPA reactivity-positive compared to ACPA reactivity-negative patients. ACPA reactivity levels decreased after 3 months of DMARD treatment, most pronounced for fibrinogenβ 60-74 to 62% of baseline antibody level, with least change in filaggrin 307-324 to 81% of baseline antibody level, both p < 0.001. However, outcomes in disease activity measures, ultrasound and ...